Photodynamic therapy of melanoma skin cancer using carbon dot – chlorin e6 – hyaluronate conjugate. (15th October 2015) - Beack, Songeun; Kong, Won Ho; Jung, Ho Sang; Do, In Hwan; Han, Seulgi; Kim, Hyemin; Kim, Ki Su; Yun, Seok Hyun; Hahn, Sei Kwang
Graphical abstract: Abstract: Despite wide application of photodynamic therapy (PDT) for the treatment of melanoma skin cancers, there are strong biomedical unmet needs for the effective generation of singlet oxygen after targeted delivery of photosensitizers. Here, we investigated a facile PDT of melanoma skin cancer using transdermal carbon dot – chlorine e6 – hyaluronate (Cdot-Ce6-HA) conjugates. The Cdot-Ce6-HA conjugate was synthesized by the coupling reaction of diaminohexane modified HA (DAH-HA) with the carboxylic group of Ce6. The singlet oxygen generation of Cdot-Ce6-HA conjugates in aqueous solution was more significant than that of free Ce6. The enhanced transdermal and intracellular delivery of Cdot-Ce6-HA conjugates to B16F10 melanoma cells in tumor model mice were corroborated by confocal microscopy and two-photon microscopy. The laser irradiation after topical treatment with Cdot-Ce6-HA conjugates resulted in complete suppression of melanoma skin cancers. The antitumor effect was confirmed by histological analysis with H&E staining and TUNEL assay for tumor apoptosis. Taken together, we could confirm the feasibility of Cdot-Ce6-HA conjugate for transdermal PDT of melanoma skin cancers. Statement of Significance: To our knowledge, this is the first report on a facile transdermal photodynamic therapy (PDT) of melanoma skin cancer using carbon dot – chlorine e6 – hyaluronate (Cdot-Ce6-HA) conjugates. We found that the singlet oxygen generation of Cdot-Ce6-HA conjugates in aqueous solution was more significant than that of free Ce6. Confocal microscopy and two-photon microscopy clearly confirmed the enhanced transdermal and intracellular delivery of Cdot-Ce6-HA conjugates to B16F10 melanoma cells in tumor model mice. Taken together, we could confirm the feasibility of Cdot-Ce6-HA conjugate for transdermal PDT of melanoma skin cancers.